2011
DOI: 10.1111/j.1472-765x.2011.03160.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel surface display system for heterogonous proteins on Lactobacillus plantarum

Abstract: Aims:  To establish a novel cell surface display system that would enable the display of target proteins on Lactobacillus plantarum. Methods and Results:  BlastP analysis of the amino acids sequence data revealed that the N‐terminus of the putative muropeptidase MurO from L. plantarum contained two putative lysin motif (LysM) repeat regions, implying that the MurO was involved in bacterial cell wall binding. To investigate the potential of MurO for surface display, green fluorescent protein (GFP) was fused to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…It has been demonstrated that hybrid PA fusions exhibit similar properties [Bosma et al, 2006;Raha et al, 2005;Steen et al, 2003]. Also LysM domains of other Gram-positive bacteria bind heterologous proteins to the cell wall peptidoglycan [Hu et al, 2010;Turner et al, 2004;Xu et al, 2011].…”
mentioning
confidence: 99%
“…It has been demonstrated that hybrid PA fusions exhibit similar properties [Bosma et al, 2006;Raha et al, 2005;Steen et al, 2003]. Also LysM domains of other Gram-positive bacteria bind heterologous proteins to the cell wall peptidoglycan [Hu et al, 2010;Turner et al, 2004;Xu et al, 2011].…”
mentioning
confidence: 99%
“…These include the bacteriophage endolysin Lyb5 (20) and the muropeptidase MurO from Lactobacillus plantarum (21). Differences in the ability to bind LysM repeat-containing proteins have been observed between Lactobacillus species, which reflect the differences in lactobacillus surfaces (22).…”
mentioning
confidence: 99%
“…Similarly, the PMB domains of archaeal hydrolases (PeiW and PeiP) allow binding of the enzymes to pseudomurein, facilitating hydrolysis by the catalytic domains (Luo et al 2002; Steenbakkers et al 2006; Visweswaran et al 2010). In recent years, the LysM domains have been widely applied for various biotechnological purposes such as in the preparation of oral influenza vaccine and for surface display of heterologous proteins on bacterial cell surfaces (Bosma et al 2006; Okano et al 2008; Shao et al 2009; Hu et al 2010; Saluja et al 2010; Xu et al 2011). Similarly, the PMB domain could be employed for the display of target proteins on pseudomurein-containing archaeal cell surfaces; it could also be used as a marker protein to identify pseudomurein-containing methanogens from their counterparts.…”
Section: Discussionmentioning
confidence: 99%